Physical Constraints and Forces Involved in Phagocytosis - Jaumouillé, Valentin; Waterman, Clare M. (Frontiers in Immunology, 2020)
Phagocytosis is a specialized process that enables cellular ingestion and clearance of microbes, dead cells and tissue debris that are too large for other endocytic routes. As such, it is an essential component of tissue homeostasis and the innate immune response, and also provides a link to the adaptive immune response. However, ingestion of large particulate materials represents a monumental task for phagocytic cells. It requires profound reorganization of the cell morphology around the target in a controlled manner, which is limited by biophysical constraints. Experimental and theoretical studies have identified critical aspects associated with the interconnected biophysical properties of the receptors, the membrane and the actin cytoskeleton that can determine the success of large particle internalization. In this review, we will discuss the major physical constraints involved in the formation of a phagosome. Focusing on two of the most-studied types of phagocytic receptors, the Fc receptors and the complement receptor 3 (αMβ2 integrin), we will describe the complex molecular mechanisms employed by phagocytes to overcome these physical constraints.